KONSEP MAHAR DALAM KOMPILASI HUKUM ISLAM RELEVANSINYA DENGAN AL QUR’AN DAN AS SUNNAH - Muhammad Ainul Yaqin; Tirmidzi Tirmidzi (LPPM STAI Muhammadiyah Probolinggo, 2021)
The dowry is of the virtue of Islam in protecting and honoring women by sharing the rights they ask for in a marriage in the form of a dowry, the size which is formalized with the agreement of both parties, the research procedure uses normative, sourced from the syari'ah district, this research focuses on the process Research in the city of Probolinggo literature, judging from the results of this study dowry in KHI and al-qur'an as well as the Sunnah at this time is suitable, from scholars such as the Malik Imam and Shafiiyyah agree that there is no optimal in offering dowries and there are also comments in it